2022
DOI: 10.1039/d1dt03113a
|View full text |Cite
|
Sign up to set email alerts
|

State of the art developments and prospects of metal–organic frameworks for energy applications

Abstract: The progress of cleaner and ecological transformation and storage of energy technologies to combat effluence or pollution and the impending energy dilemma has recently fascinated the interest of the energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 305 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…MOFs are a class of crystalline porous materials constituted by rigid and even flexible organic ligands coordinated through Coulombic and/or coordinative bonds to metal ions or metal clusters. Initially, MOFs were tested for gas adsorption and separation, but immediately the potential of these materials in other areas and particularly for catalysis and photocatalysis was recognized. Particularly, the use of MOFs as photocatalysts has attracted a large interest due to the combination of unique properties that MOFs meet. Among them, the most important ones are light harvesting by tunable organic linkers and efficient charge separation due to the intimate contact between the linkers and nodal metals. , The reader is referred to some existing reviews dealing with the MOFs as photocatalysts for different applications other than OWS, including water treatment, pollutant degradation, , and solar fuels ,, production among others. …”
Section: Mofs As Photocatalysts For Ows Under Visible Light Irradiationmentioning
confidence: 99%
“…MOFs are a class of crystalline porous materials constituted by rigid and even flexible organic ligands coordinated through Coulombic and/or coordinative bonds to metal ions or metal clusters. Initially, MOFs were tested for gas adsorption and separation, but immediately the potential of these materials in other areas and particularly for catalysis and photocatalysis was recognized. Particularly, the use of MOFs as photocatalysts has attracted a large interest due to the combination of unique properties that MOFs meet. Among them, the most important ones are light harvesting by tunable organic linkers and efficient charge separation due to the intimate contact between the linkers and nodal metals. , The reader is referred to some existing reviews dealing with the MOFs as photocatalysts for different applications other than OWS, including water treatment, pollutant degradation, , and solar fuels ,, production among others. …”
Section: Mofs As Photocatalysts For Ows Under Visible Light Irradiationmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) composed of a broad range of organic ligands and metal species have been widely explored as sacrificial templates for the synthesis of various hollow materials owing to their simple fabrication, porous structure, and ease of tunability. 49,50 The ZIFs are the subclass of MOFs and have received great interest. 51,52 Previous studies revealed that ZIF-8 made of zinc metal nodes and a 2methylimidazole linker can be utilized as a sacrificial template to fabricate zinc-based oxides and sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Although the conductivity of MOFs has been greatly increased by combining them with highly conductive materials, most of the materials reported in the past are powders which rely on non-conductive adhesives to combine with the current collector. 19 This inevitably affects the holistic conductivity of the electrode. Therefore, directly growing MOF/highly conductive material composites on a current collector might be a feasible method to obtain high energy density electrodes with low electrical resistivity.…”
Section: Introductionmentioning
confidence: 99%